The Influence of Brand Image, Social Environment and Cult Brand on Behavioral Intention of Smartphone Users - Marsya Safira Sutrisno,; Fatma Yufita Melisiana Angkasapuri,; Vini Marianie Vici,; Willy Gunadi, (Jurnal Manajemen, 2023)
Entering the current digital and globalization era, people socialize using communication technology in all their activities. This makes the technology and communication industry develop very rapidly, one of which is the smartphone. This study aims to determine the effect of brand image on behavioural intention, the influence of social environment on behavioural intention, and the influence of brand cult on behavioural intention. This research was conducted by distributing questionnaires online to research samples domiciled in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) and have used the same smartphone for three years. A total of 233 respondents were collected using a purposive sampling technique. This study was analyzed using the PLS-SEM method. The results of this study indicate that brand image and brand cult have a positive and significant effect on behavioural intention. In contrast, the social environment has a positive but insignificant effect on behavioural intention. This shows that brand image and culture have a big impact on the smartphone industry and are determining factors that attract consumers to repurchase smartphone products. Based on the research results, the company is expected to be able to express its activities through marketing that consumers can realize and can also build a product that can meet the needs and desires of consumers. Companies must also have a differentiator from other brands outside of product, delivery, messaging, or marketing strategies.